2017
DOI: 10.1080/13561820.2017.1395828
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians’ perspectives on interprofessional teamwork: Findings from a qualitative study

Abstract: The aim of this study was to describe family physicians' perspectives of their role in the primary care team and factors that facilitate and hinder teamwork. A qualitative study was conducted employing individual interviews with 19 academic/community-based family physicians who were part of interprofessional primary care teams in Edmonton, Alberta, Canada. Professional responsibilities and roles of physicians within the team and the facilitators and barriers to teamwork were investigated. Interviews were audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Characteristics and attributes that facilitate effective teams and the function of those teams have been well documented in the literature (Grace et al, 2017;Szafran et al, 2018) (Nancarrow et al, 2013). A number of team attributes including communication, leadership and understanding the roles of others were considered key.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics and attributes that facilitate effective teams and the function of those teams have been well documented in the literature (Grace et al, 2017;Szafran et al, 2018) (Nancarrow et al, 2013). A number of team attributes including communication, leadership and understanding the roles of others were considered key.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, practical factors, such as the geography of the workplace and work schedule, can impact the accessibility of team members, which can hinder the teamworking process (Delva, Jamieson, & Lemieux, 2008;S Reeves, Lewin, Espin, & Zwarenstein, 2010;Sargeant et al, 2008). As face-to-face communication is not always possible, there is then a greater need for effective communication using a range of processes to support information sharing and exchange within a team; central coordinators such as secretaries are seen as central to facilitating communication because they interacted with all team members (Aungst & Belliveau, 2015;Azar et al, 2017;Bardach, Real, & Bardach, 2017;Delva et al, 2008;Kuziemsky & Reeves, 2012;Szafran, Torti, Kennett, & Bell, 2018).…”
Section: Interprofessional Teamworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have evaluated the relational, processual, organisational and contextual dimensions of professional collaboration, inspired by Reeves et al’s framework for inter-professional collaboration [14]. Previous application of this framework has been used, for example, in studies describing the perspectives of GPs of their role in the primary care team, the factors that facilitate and hinder teamwork [15] and in examining the perspectives and experiences of family health team members regarding inter-professional collaboration and perceived benefits [16]. …”
Section: Introductionmentioning
confidence: 99%
“…a study of physicians' perspectives on interprofessional teamwork found that family physicians also see themselves as the team leaders. 29 The College of Family Physicians of Canada advocates for family physicians being the 'most responsible provider' within the Patient-Centered Medical Home, 2 hence in the leadership role. Other health professionals have different perspectives on team leadership, which can result in tensions in professional relationships.…”
Section: Discussionmentioning
confidence: 99%